Uncertainty-Aware Few-Shot Image Classification - Zhang, Zhizheng; Lan, Cuiling; Zeng, Wenjun; Chen, Zhibo; Chang, Shih-Fu (International Joint Conference on Artificial Intelligence (IJCAI 2021), 2021)
Few-shot image classification aims to learn to recognize new categories from limited labelled data. Recently, metric learning based approaches have been widely investigated which classify a query sample by finding the nearest prototype from the support set based on the feature similarities. For few-shot classification, the calculated similarity of a query-support pair depends on both the query and the support. The network has different confidences/uncertainty on the calculated similarities of the different pairs and there are observation noises on the similarity. Understanding and modeling the uncertainty on the similarity could promote better exploitation of the limited samples in optimization. However, this is still underexplored in few-shot learning. In this work, we propose Uncertainty-Aware Few-Shot (UAFS) image classification by modeling uncertainty of the similarities of query-support pairs and performing uncertainty-aware optimization. Particularly, we design a graph-based model to jointly estimate the uncertainty of similarities between a query and the prototypes in the support set. We optimize the network based on the modeled uncertainty by converting the observed similarity to a probabilistic similarity distribution to be robust to observation noises. Extensive experiments show our proposed method brings significant improvements on top of a strong baseline and achieves the state-of-the-art performance.